2020
DOI: 10.1101/2020.04.02.022509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunity to infections in arboviral vectors by integrated viral sequences: an evolutionary perspective

Abstract: In the model organism Drosophila melanogaster, the PIWI-interacing RNA pathway contributes in silencing transposable elements (TEs) through smallRNAs (piRNAs), which arise from genomic loci (piRNA clusters) that contain sequences of previously-acquired TEs. As such, they are a functionally-immune archive of previous TE invasions that is passed to the offspring. In the arboviral vector Aedes aegypti, piRNA clusters contain TEs and endogenous viral elements from nonretroviral RNA viruses (nrEVEs) which produce p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Such association does not appear to be only a physical co-localization, but a result of putative antiviral mechanism mediated by the activity of some retrotransposon elements (Whitfield et al, 2017;Tasseto et al, 2019). Lastly, Crava et al (2020) have shown that TEs from BEL-Pao superfamily are enriched into piRNA clusters found in the AaegL5 Ae. aegypti genome assembly and this enrichment can influence their association with EVEs.…”
Section: Introductionmentioning
confidence: 90%
“…Such association does not appear to be only a physical co-localization, but a result of putative antiviral mechanism mediated by the activity of some retrotransposon elements (Whitfield et al, 2017;Tasseto et al, 2019). Lastly, Crava et al (2020) have shown that TEs from BEL-Pao superfamily are enriched into piRNA clusters found in the AaegL5 Ae. aegypti genome assembly and this enrichment can influence their association with EVEs.…”
Section: Introductionmentioning
confidence: 90%
“…These non-retroviral sequence elements are enriched in piRNA clusters and, accordingly, give rise to abundant piRNAs (26), which may guide the slicing of cognate RNA from acutely infecting viruses. It has been recently shown that piRNAs derived from EVEs are indeed able to target and inhibit newly infecting viruses (31)(32)(33)), yet, it remains unknown whether piRNA phasing may serve as a mechanism to expand the vpiRNA pool after an initial cleavage by an endogenous, possibly EVE-derived, piRNA.…”
Section: A Subset Of Responder Pirnas Undergoes Nibbler-mediated Trimmentioning
confidence: 99%
“…aegypti piRNA pathway differs from that in Drosophila in three important ways: i) the pathway is active in somatic tissues as well as germline tissues (21,22), ii) it processes noncanonical substrates such as de novo produced viral RNA (23)(24)(25), and iii) mosquito piRNA clusters contain large numbers of endogenous viral elements (EVEs): sequences of nonretroviral RNA viruses inserted in mosquito genomes (26)(27)(28). These EVEs give rise to abundant piRNAs (26,29,30) and mediate antiviral defense (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, integrated viral sequences in both plants and animals derive not only from DNA viruses and retroviruses but also from non-retroviral RNA viruses and are enriched in repetitive regions of the genome (20,(23)(24)(25)28). To understand the widespread distribution of EVEs and their biological role, we need to characterize EVEs using WGS data from wild-collected samples or samples collected under hypothesis-driven experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally EVEs of non-model organisms tend to occur in repetitive DNA, mostly in association with transposable element (TE) sequences and in Piwi-interacting RNA (piRNA) clusters (20,23,24). These newly-identified EVEs have been increasingly recognized as important players in different biological processes such as antiviral immunity and regulation of expression (25,26).…”
Section: Introductionmentioning
confidence: 99%